Association between supportive attitude and adoptive practice of control strategy against COVID-19 amosng college students in China: a cross-sectional study - Dong Shen; Dan Liu; Miaochun Cai; Peiliang Chen; Zhenghe Wang; Yujie Zhang; Zhihao Li; Xiru Zhang; Xianbo Wu; Xingfen Yang; Chen Mao (BMC, 2021)
Abstract Background We investigated college students' attitude and compliance towards a prevention strategy involving use of non-pharmaceutical interventions (NPIs) against coronavirus disease 2019 (COVID-19). Methods We conducted a cross-sectional online survey in four universities in Guangdong Province (China) based on purposive sampling. A self-administered questionnaire was given to College students (CSs) to measure the supportive attitude towards an outbreak control strategy and adoption of NPIs in respondents. Results A total of 44,446 CSs participated between 31 January and 10 February 2020; 92.7% of respondents supported the outbreak control strategy. The proportion of respondents who avoided public places, wore a facemask, avoid gatherings, and washed hands more frequently than usual was 94.8, 92.8, 91.2 and 86.9%. respectively. A total of 76.5% respondents adopted all four measures. A supportive attitude was associated with NPI adoption. Students who were female, postgraduate, anxious, and not depressed tended to have a higher supportive attitude and higher chance of NPI adoption. Conclusions Higher supportiveness towards the disease control strategy for the Chinese public may lead to higher adoption rate of NPIs. Psychosocial factors were related to a supportive attitude and adoption of the NPI. We believe that our findings could aid policymakers to create NPIs to prevent and control emerging infectious diseases such as COVID-19.